Answer:
second option
Step-by-step explanation:
Given
f(x) = (x - 7)(x + 4)(3x - 2)
To find the zeros let f(x) = 0, that is
(x - 7)(x + 4)(3x - 2) = 0
Equate each factor to zero and solve for x
x - 7 = 0 ⇒ x = 7
x + 4 = 0 ⇒ x = - 4
3x - 2 = 0 ⇒ 3x = 2 ⇒ x = ![\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
zeros are x = - 4, x =
, x = 7
Answer:
84 c. –25 6. 119 7. –28 36 8a. 4 b. 52 LESSON EI.B: ANSWERS 709 Topic EI .... The length is 11 inches, and the width is 7 inches. ... 15x – 10 = 2x + 6 1 5 10. x = 1 11. y = 8x – 5 12. x = y + 8 8 49. .... 5xy 3 – 17x 2y + 8xy + 16x 3y – 7x 10. x 3y 2z – 10x 2y + 14x 2z + 3xy 2 – 25xz 2 LESSON ... 2 > y > –5 F a 4x 3 y 5 4y 3 x 22.
Step-by-step explanation:
Answer:
5
Step-by-step explanation:
90 fries in 18 minutes. You would divide 90 by 18 to get the answer of 5 fries per minute.
Answer:
5
Step-by-step explanation:
You save ⅓ of entry fee, so you save 1.20 and you pay 2.40. We only really care about the 1.20 reduction. 5 / 1.2 = 4.16 so he must go 5 times to get the 5 back